2015
DOI: 10.1111/cen.12761
|View full text |Cite
|
Sign up to set email alerts
|

Importance of contralateral aldosterone suppression during adrenal vein sampling in the subtype evaluation of primary aldosteronism

Abstract: In patients with PA, where the LI is <4 on AVS, CL suppression of aldosterone is an accurate predictor of a unilateral source of aldosterone excess. CL suppression data should be interpreted in conjunction with computed tomographic adrenal imaging findings to guide surgical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 29 publications
6
35
6
Order By: Relevance
“…The aldosterone gradient in the gray zone (LI=2-4) should be carefully interpreted in the subtype diagnosis of PA to avoid inappropriate adrenalectomy. 13 Additional criteria such as contralateral adrenal aldosterone suppression 15 and clinical and biochemical findings 11 should be taken into account when considering patients for adrenal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aldosterone gradient in the gray zone (LI=2-4) should be carefully interpreted in the subtype diagnosis of PA to avoid inappropriate adrenalectomy. 13 Additional criteria such as contralateral adrenal aldosterone suppression 15 and clinical and biochemical findings 11 should be taken into account when considering patients for adrenal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Young et al 24 demonstrated that contralateral adrenal aldosterone suppression is seen in 95% of the patients with unilateral PA. In addition, Umakoshi et al 15 demonstrated a clinical significance of contralateral adrenal aldosterone suppression for prediction of unilateral PA especially when LI is <4. It is, therefore, suggested that the 2 patients with contralateral adrenal aldosterone suppression could be PA with false-negative results in both of CCT and SIT.…”
Section: Discussionmentioning
confidence: 99%
“…Monticone et al, in a large multicenter study, reported no significant differences in terms of the biochemical and clinical response after an adrenalectomy between patients with and without contralateral aldosterone suppression and an LI ≥ 4 [72]. The clinical significance of CR < 1 in patients with a 2 < LI < 4 was investigated by Umakoshi et al in a small cohort of 29 patients [73]. The authors reported a significant difference in terms of the overall cure rate of PA between patients with and without contralateral suppression (81% versus 31%), pointing out a possible major usefulness of CR in evaluating the “grey zone” of AVS results.…”
Section: Avs Interpretation Criteriamentioning
confidence: 99%
“…Interestingly, diagnosis of unilateral PA confirmed by AVS was never found to be a predictor of good outcome after surgery, and patients with a higher lateralization index on AVS do not have a better outcome [29]. Contralateral suppression on AVS correlated with good BP and biochemical outcomes from surgery in some [33,34], but not in all studies [35].…”
Section: Predictors Of Cure or Persistent Hypertensionmentioning
confidence: 99%